Analysis of Factors That Influence Customer Decisions in Choosing Tabot Savings Products (Case Study of Bank Bengkulu Main Branch) - Deri; Suwarni; Silke Sachanovrissa (Penerbit Jurnal Indonesia, 2025)
This research was conducted considering the increasingly tight competition in the banking industry, making an understanding of the factors influencing customer satisfaction very important for maintaining customer loyalty. Bank Bengkulu introduced the Tabot Savings product, a product inspired by the local culture of Bengkulu, to enhance customer appeal and trust. This study aims to determine the influence of product quality, service quality, and trust quality on customer satisfaction at Bank Bengkulu Main Branch both simultaneously and partially. The analysis methods used include validity tests, reliability tests, multiple linear regression, coefficient of determination, F-test, and t-test. Data collection was conducted using questionnaires. The sample for this study consisted of 100 customers of Bank Bengkulu Main Branch. Product quality, service quality, and trust quality have a significant simultaneous effect on customer satisfaction at Bank Bengkulu Main Branch, as the significance value is 0.000 < 0.05. Product quality has a significant partial effect on customer satisfaction at Bank Bengkulu Main Branch, as the significance value is 0.031 < 0.05. Service quality has a significant partial effect on customer satisfaction at Bank Bengkulu Main Branch, as the significance value is 0.003 < 0.05. Trust has a significant partial effect on customer satisfaction at Bank Bengkulu Main Branch, as the significance value is 0.001 < 0.05.